ANALISIS STRUKTURALISME NASKAH DRAMA TARLING â€œDOKTER PALSUâ€ KARYA HJ. DARIYAH - Saroni (Bahtera Indonesia, 2019)
Tarling is a musical intellectual that contributes to the uplift of Indramayu's cultural arts. According to Hidayatulla (2005) the art of tarling still exists and is developing, but its existence does not receive much attention from the community, especially the younger generation. The cultural development is emphasized by Maknum (2004: 81) the process of art development is influenced by several factors namely scientific, environmental, and time factors. All three take place interactively. As a cultural product, art in its development will be subject to the main laws that govern human development. The diversity of Tarling music that continues to change and develop in the wider community, is feared to reduce the function of identity, as well as undergoing changes in shape which ultimately is not impossible that will farther and lose its original form. The main objective of this research is an effort in the inheritance and preservation of Indramayu culture by realizing the design of the staging of the Tarling drama script "Fake Doctor" by Hj. Dariyah by analyzing the structure of the Tarling drama script "Fake Doctor" by Hj. Dariyah covers the analysis of themes, characterizations, and plot. The study was designed in 1 (one) year using qualitative methods. This research provides a fundamental contribution related to a field of science through the performance of the Tarling drama script "Fake Doctor" by Hj. Dariyah. First, students who are involved as drama players not only get literary theory in lectures, but students also gain experience in practicing literary science in a performance. Second, the results of this study can be used as an alternative to be staged in the tarling groups throughout Indramayu Regency. Third, the results of this study can be taken into consideration for local governments related to the cultural heritage and preservation of Indramayu. Tarling merupakan karya intelektual musik yang memberikan andil mengangkat nilai seni budaya Indramayu. Menurut Hidayatulla (2005) seni tarling masih ada dan berkembang, tetapi keberadaannya kurang mendapatkan perhatian dari masyarakat terutama generasi muda. Perkembangan budaya tersebut dipertegas oleh Maknum (2004:81) proses perkembangan seni dipengaruhi oleh beberapa faktor yaitu faktor ilmiah, lingkungan, dan waktu. Ketiganya berlangsung secara interaktif. Sebagai produk kebudayaan, kesenian dalam perkembangannya akan tunduk kepada hukum-hukum utama yang mengatur perkembangan manusia. Beragamnya musik Tarling yang terus berubah dan berkembang di masyarakat luas, dikhawatirkan mengurangi fungsi identitas, serta mengalami perubahan bentuk yang akhirnya bukan mustahil akan semakin jauh dan kehilangan bentuk aslinya. Tujuan utama penelitian ini adalah upaya dalam pewarisan dan pemertahanan budaya Indramayu dengan cara merealisasikan rancangan pementasan naskah drama tarling â€œDokter Palsuâ€ Karya Hj. Dariyah dengan menganalisi struktur naskah drama tarling â€œDokter Palsuâ€ Karya Hj. Dariyah meliputi analisis tema, penokohan, dan alur. Penelitian dirancang dalam 1 (satu) tahun menggunakan metode kualitatif. Penelitian ini memberikan kontribusi mendasar terkait suatu bidang ilmu melalui pementasan naskah drama tarling â€œDokter Palsuâ€ Karya Hj. Dariyah. Pertama, mahasiswa yang terlibat sebagai pemain drama tidak hanya mendapatkan teori sastra saja pada perkuliahan, namun mahasiswa juga memeroleh pengalaman dalam mempraktikan ilmu sastra dalam sebuah pementasan. Kedua, hasil penelitian ini dapat dijadikan alternatif untuk dipentaskan pada group tarling se-Kabupaten Indramayu. Ketiga, hasil penelitian ini dapat dijadikan bahan pertimbangan bagi pemerintah daerah terkait dengan pewarisan dan pemertahanan budaya Indramayu.